2016
DOI: 10.1093/nar/gkw868
|View full text |Cite
|
Sign up to set email alerts
|

COEXPEDIA: exploring biomedical hypotheses via co-expressions associated with medical subject headings (MeSH)

Abstract: The use of high-throughput array and sequencing technologies has produced unprecedented amounts of gene expression data in central public depositories, including the Gene Expression Omnibus (GEO). The immense amount of expression data in GEO provides both vast research opportunities and data analysis challenges. Co-expression analysis of high-dimensional expression data has proven effective for the study of gene functions, and several co-expression databases have been developed. Here, we present a new co-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 34 publications
0
92
0
Order By: Relevance
“…First, netNMF-sc relies on existing gene-gene networks. While we have demonstrated that generic gene-gene co-expression networks [Yang et al, 2016] can improve clustering performance of human and mouse scRNA-seq data, netNMF-sc may not offer substantial improvements over existing methods on tissues or organisms where high-quality gene-gene networks are not available. In the future, other prior knowledge could be incorporated into netNMF-sc, such as cell-cell correlations, which might be obtained from underlying knowledge of cell types or from spatial or temporal information.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…First, netNMF-sc relies on existing gene-gene networks. While we have demonstrated that generic gene-gene co-expression networks [Yang et al, 2016] can improve clustering performance of human and mouse scRNA-seq data, netNMF-sc may not offer substantial improvements over existing methods on tissues or organisms where high-quality gene-gene networks are not available. In the future, other prior knowledge could be incorporated into netNMF-sc, such as cell-cell correlations, which might be obtained from underlying knowledge of cell types or from spatial or temporal information.…”
Section: Discussionmentioning
confidence: 89%
“…To quantify the contribution of the network information to the performance of netNMF-sc, we ran netNMF-sc with three additional networks: a generic gene-gene co-expression network from Coexpedia [Yang et al, 2016], a K-nearest neighbors network (KNN), and a random network with the same degree distribution as the ESCAPE network. The K-nearest neighbors network was constructed by placing an edge between the ten nearest neighbors of each gene in the input data matrix X, based on Euclidean distance.…”
Section: Evaluation On Cell Clusteringmentioning
confidence: 99%
See 2 more Smart Citations
“…5606 literatures were exported and the document types involved in ARTICLE and REVIEW, improving the comprehensive feature of our research. Medical subjects Headings (MeSH) terms express the main idea of a literature, identified for the following co-word associated analysis [9].…”
Section: Data Source and Collectionmentioning
confidence: 99%